Randomized trial of telehealth delivery of cognitive-behavioral treatment for insomnia vs. in-person treatment in veterans with PTSD - Philip Gehrman; Holly Barilla; Elina Medvedeva; Scarlett Bellamy; Erin O'Brien; Samuel T. Kuna (Journal of Affective Disorders Reports, 2020)
Background: Insomnia is prevalent in veterans with PTSD but often goes untreated. Cognitive behavioral therapy for insomnia (CBT-I) is an efficacious treatment but many patients do not have access to this intervention. Clinical video telehealth provides a means of increasing access to care but there is a need to understand the effectiveness of care delivered using this modality. Methods: Randomized non-inferiority trial comparing group CBT-I delivered between VA clinics over video telehealth to in-person treatment. 116 Veterans with PTSD received CBT-I over six weeks in a group format at a VA healthcare facility. The Insomnia Severity Index (ISI) was the primary outcome measure. Secondary outcomes included measures of sleep, PTSD severity and quality of life. The non-inferiority margin was defined as a difference in ISI change scores between groups ≥1.67 points. Results: The mean(SD) improvement in the ISI was 6.48 (0.90) points for in-person treatment and 4.45 (0.98) points for telehealth treatment in intent-to-treat analyses. In both intent-to-treat and per-protocol analyses, the difference between these change scores of 2.03 had a confidence interval that included the non-inferiority margin of 1.67, supporting the hypothesis of non-inferiority. On secondary outcomes, there were significant improvements after treatment only in sleep quality and no between-group differences. Limitations: The eligibility criteria were intentionally broad, so there were several potential confounding factors. Drop-out was also considerable, with only 54.3% of subjects in the in-person group and 46.9% in the telehealth group completing treatment. Conclusions: Delivery of group CBT-I by clinical video telehealth to veterans with PTSD is non-inferior to in-person treatment, although overall efficacy of treatment was modest. Telehealth technology can increase access to care without sacrificing clinical gains.